Adjacency Pairs Analysis on Teaching-Learning Process - Indarti, Gatri Asti Putri (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This research is proposed to analyze adjacency pairs in teaching-learning process functioning as a unit of Conversation Analysis (CA). In a classroom, interaction between teacher and students involves appropriate expressions intended to get a meaningful and interactive teaching-learning process. Those expressions including responses are called adjacency pairs. In this research, the interaction between the teacher and the students in adult class at BBC ETS (English Training Specialist) Semarang 2, Tlogosari was observed. The results showed that the types of adjacency pairs of the teacher used are question (54%), assessment (24%), command (8%), summons (5%), compliment (3%), greeting (3%), request (2%), and leave-taking (1%). The teacher mostly used questions to make sure that the students understand about the materials. In addition, the students mostly answered with preferred responses; expected answer of a question (41%), agreement of an assessment (21%), compliance of a command (6%), greeting (3%), acceptance of a request (3%), and leave-taking (1%). The dis-preferred responses expressed by the students are unexpected answer of a question (13%), non-response summons (5%), disagreement of an assessment (3%), rejection of a compliment (3%), and incompliance of a command (2%). Based on the results, the researcher suggests all teachers to make interaction interactively by using appropriate types of adjacency pairs like question, assessment, and other types suited class conditions. Moreover, they should express more on compliment as students also need an appreciation. In short, types of adjacency pairs should be applied properly in teaching-learning process.